2016
DOI: 10.1103/physrevd.93.125029
|View full text |Cite
|
Sign up to set email alerts
|

B-mode polarization of the CMB and the cosmic neutrino background

Abstract: It is known that in contrast with the E-mode polarization, the B-mode polarization of the Cosmic Microwave Background cannot be generated by the Compton scattering in the case of scalar mode of metric perturbation. However it is possible to generate the B-mode by the Compton scattering in the case of tensor mode of metric perturbation. For this reason, the ratio of tensor to scalar modes of metric perturbation (r ∼ C Bl /C El ) is estimated by comparing the B-mode power spectrum with the E-mode at least for sm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…1. The fifth diagram in which two fermions directly couple to two photons is given in (21). Therefore, the amplitude of the Compton scattering in the NCQED can be given as…”
Section: Stokes Parameters and Boltzmann Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…1. The fifth diagram in which two fermions directly couple to two photons is given in (21). Therefore, the amplitude of the Compton scattering in the NCQED can be given as…”
Section: Stokes Parameters and Boltzmann Equationmentioning
confidence: 99%
“…Furthermore, the Compton scattering in the presence of a background can potentially lead to a B-mode polarization for the CMB even for the scalar perturbation. The contribution to the observed B-mode spectrum from the interaction between CMB photon and the cosmic neutrino background (CNB) in the scalar perturbation background has been considered in [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Some of our recent works also discussed the generation of B-mode polarization in the presence of scalar perturbations via Cosmic Neutrino Background and CMB interactions [47,59,60], nonlinear photons interactions [61], photon interaction by considering extensions to QED such as Lorentzinvariant violating operators [62], non-commutative geometry [49], interaction of dipolar dark matter with CMB photons [63] and photon-fermion forward scattering [64]. Also the intrinsic B-mode polarization is calculated by using the Boltzmann code SONG [65] which induce in the CMB by the evolution of primordial density perturbations at second order [66].…”
Section: Introductionmentioning
confidence: 99%
“…As the new sources, for instance, in [36] the effect of the Faraday rotation due to the uniform magnetic field on the CMB is investigated and it is shown that a nonvanishing Bmode polarization can be produced through Faraday rotation. In [37,38], the authors have discussed that photon-neutrino interaction in the presence of scalar perturbations could be considered as one of the sources of the CMB B-mode polarization. It is also shown that the Compton scattering in the non-commutative space-time can generate the B-mode polarization of the CMB [39] and the possibility of the producing B-mode polarization pattern due to polarized Compton scattering in the presence of scalar perturbations has been discussed in [40].…”
Section: Introductionmentioning
confidence: 99%